2007
DOI: 10.1017/s0266462307051598
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of cardiovascular disease: Cost-effectiveness comparison

Abstract: A cost-effective strategy should offer smoking cessation for smokers and aspirin for moderate and high levels of risk among men 45 years of age and older. Statin therapy is the most expensive option in primary prevention at levels of 10-year coronary heart disease risk below 30 percent and should not constitute the first choice of treatment in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…However, inconsistencies exist at lower levels. [6,7,36] Franco et al [9,37] reviewed 24 studies of costeffectiveness analyses of statins. Estimated ratios increase with decreasing risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inconsistencies exist at lower levels. [6,7,36] Franco et al [9,37] reviewed 24 studies of costeffectiveness analyses of statins. Estimated ratios increase with decreasing risk.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] For instance, a previous study on the cost effectiveness of four risklowering interventions (smoking cessation, antihypertensives, aspirin [acetylsalicylic acid], and statins) in the primary prevention of cardiovascular disease showed statins to be the least cost effective (h73 971 to h190 276 per year of life saved). [9] Statin therapy has also been shown to be cost effective for high levels of CHD risk, but inconsistencies exist at lower levels. [10] Finally, several guidelines regarding management of subjects with high CHD risk have been issued but, to our knowledge, their economic impact has never been compared.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] A decision analysis reported that routine use of low-dose aspirin is as likely to be associated with benefit as harm, but that analysis was limited to elderly people without cardiovascular disease. 8 Previous cost-effectiveness analyses that examined the threshold to recommend aspirin reported that its use was warranted from a 10-year cardiovascular disease risk that varied between 7.5% and 15%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous decision analyses and economic evaluations have shown that the decision of whether to take aspirin as the primary prevention for cardiovascular events depends on the patients' cardiovascular risk level. [7][8][9][10][11][12][13][14][15] Recently, a meta-analysis of the role of aspirin in the primary prevention of cardiovascular events revealed important differential effects of aspirin therapy between men and women. 5 Aspirin reduced the risk of myocardial infarction in men and that of ischemic stroke in women.…”
Section: Editorial P 2844 Clinical Perspective P 2883mentioning
confidence: 99%
“…4 Smoking cessation has also been found to be A call to action: new treatment options provide even more reasons to intervene in tobacco dependence Robert the most cost-effective therapy for the primary prevention of CVD in men compared with aspirin, antihypertensives, and statins. 5 Although it should be obvious to cardiologists that a combination of pharmacotherapy and counseling is the best way to help their patients stop smoking, survey data indicate that many of these practitioners might not be effectively intervening in this pernicious addiction. A European study indicated that cardiovascular specialists are reluctant to take the time to intervene in tobacco dependence, and are less likely than lung physicians to advise their patients to stop smoking and to prescribe medications to treat tobacco dependence.…”
mentioning
confidence: 99%